Hybridization, agency discretion, and implementation of the U.S. Endangered Species Act. Issue 6 (25th October 2016) - Lind‐Riehl, Jennifer F.; Mayer, Audrey L.; Wellstead, Adam M.; Gailing, Oliver
Abstract: The U.S. Endangered Species Act (ESA) requires that the "best available scientific and commercial data" be used to protect imperiled species from extinction and preserve biodiversity. However, it does not provide specific guidance on how to apply this mandate. Scientific data can be uncertain and controversial, particularly regarding species delineation and hybridization issues. The U.S. Fish and Wildlife Service (FWS) had an evolving hybrid policy to guide protection decisions for individuals of hybrid origin. Currently, this policy is in limbo because it resulted in several controversial conservation decisions in the past. Biologists from FWS must interpret and apply the best available science to their recommendations and likely use considerable discretion in making recommendations for what species to list, how to define those species, and how to recover them. We used semistructured interviews to collect data on FWS biologists' use of discretion to make recommendations for listed species with hybridization issues. These biologists had a large amount of discretion to determine the best available science and how to interpret it but generally deferred to the scientific consensus on the taxonomic status of an organism. Respondents viewed hybridization primarily as a problem in the context of the ESA, although biologists who had experience with hybridization issues were more likely to describe it in more nuanced terms. Many interviewees expressed a desire to continue the current case‐by‐case approach for handling hybridization issues, but some wanted more guidance on procedures (i.e., a "flexible" hybrid policy). Field‐level information can provide critical insight into which policies are working (or not working) and why. The FWS biologists' we interviewed had a high level of discretion, which greatly influenced ESA implementation, particularly in the context of hybridization.